RANCANG BANGUN GAME EDUKASI ANAK USIA DINI PENGENALAN HURUF DAN ANGKA BERBASIS ANDROID - Wika Purbasari; Riana Safitri; Joko Purnomo (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2022)
Educational games are very interesting to develop, there are several advantages of educational games compared to conventional educational methods which are quite monotonous. The purpose of this research is to create a game application as an alternative media for learning to recognize letters and numbers. This game can be used as an alternative medium of learning in the Early Childhood Education Unit of Seruni 1 Gombong Village in changing the conventional way of learning into a way of learning with educational game media, so that it can develop children's learning processes and make learning better than before. This application uses the Waterfall development method where the process is sequential downwards. Making this educational game application using software construct 2. Researchers use learning evaluation to determine student learning progress so that researchers can find out student learning progress by using this educational game. The result of this research is to build an application as an additional medium of learning for early childhood. This study uses a product test with a test result of 85.57% and a benefit test using ULEA with a test result of 96.25% of learnability and efficiency aspects. This educational game application makes it easier for teachers to deliver material on recognizing letters and numbers to students so that students more easily understand the material presented. This educational game also makes additional interesting media for students so that students will be more interested in learning both at school and outside of school